Nomads: In Search of the Lost Path - Mustoyapova, Ainash. author. aut Link
XI, 326 p.
Keywords: The book is devoted to the problem of the civilizational development of the Kazakhs, as descendants of nomads, at the present stage. The author pays special attention to how the eras of modernity and postmodernity influenced today's Kazakhstan. In this anti-colonial polemic, the author argues in favor of finding the origin of Kazakh nomad culture prior to the colonization of Kazakhstan by imperial Russia; in exploring nomad histories, she seeks to find an alternative path. The book may be of interest to researchers studying the history, politics, sociology, culture of Central Asia and, more broadly, issues of the development of modern civilization. Ainash Mustoyapova – Candidate of Philological Sciences, Associate Professor, is the author of more than 70 scientific and educational publications, and more than 150 journalistic articles. Major works include: The Japanese Novel of the second half of the twentieth century (2022), The Modernist Novel (2022, 2024), Famine of 1931–1933 in Central Kazakhstan: collection of archival documents and memoirs (2023), Decolonization of Kazakhstan (2023), Leaders of the Nation: A Political History of Kazakhstan (2024).